Process mapping and lean thinking: a bibliometric study - Amorim, Matheus de Jesus; Xavier, Thiago Padovani (Brazilian Journal of Production Engineering, 2021)
This article analyzes the characteristics of publications related to process mapping and lean thinking. The research was carried out in the Web of Science database, seeking to examine seven thematic areas, entitled: authors, research areas, years of publication, organizations, countries / regions, funding agencies and sources of publications, in addition, a comparison was made among the most cited publications with the authors who published the most about the researched topics. During the period from 2010 to 2019, 198 articles were treated in all and, according to the results of this study, the number of publications grew significantly in much of the stipulated period, but publications related to the theme of lean thinking showed a decline in 2019.  In other words, 86.36% of the publications were written in the English language, and having as main source the journals related to health, which demonstrates the scope of application of the themes. It was also found that most authors who stood out in the number of publications do not have their work among the most cited, that is, the articles with the greatest impact on the themes studied.
Keywords: VOSviewer; Data base; Web of Science